Outcome analysis and risk factors for perioperative myocardial ischemia after elective aortic surgery - Dovzhanskiy, Dmitriy I.; Jäckel, Petra; Bischoff, Moritz; Hakimi, Maani; Hinz, Ulf; Böckler, Dittmar (Annals of vascular surgery, 2021)
Background - Perioperative myocardial ischemia (PMI) after non-cardiac surgery remains a serious postoperative complication. This study analyzed the risk factors and outcomes of patients who suffered from PMI after elective aortic surgery. - Patients and Methods - Data from 863 patients who underwent elective aortic surgery for aneurysms or Leriche syndrome were retrospectively analysed with regard to PMI. The diagnosis of PMI was based on a positive serum troponin diagnostic test. According to the clinical signs and symptoms, the patients with PMI were divided into two groups: symptomatic and asymptomatic patients. Comorbidities, preoperative medication, intraoperative parameters, postoperative complications, mortality, length of intensive care stay and hospitalisation, as well as the long-term follow-up, were compared in a matched-pair analysis (1:3) with patients without PMI. Logistic regression analyses were performed to identify independent risk factors for PMI. - Results - Thirty-two patients with PMI were identified. Cardiac comorbidities (previous myocardial ischemia, P = 0.0099; left ventricular systolic dysfunction, P = 0.0429), ASA score ≥III (P = 0.0114) and preoperative elevated creatinine (P = 0.0194) were more common in patients who suffered PMI. The regression analysis confirmed that peripheral artery disease and prolonged operative duration >180 min are significant predictors of PMI. Surgical complications (wound healing deficit, P = 0.0027; rate of secondary interventions during primary admission, P = 0.0057) and medical complications (pneumonia, P = 0.0002; renal dysfunction, P = 0.0041) were more common in patients with PMI compared to the control group. Patients who suffered PMI remained in intensive care for a significantly longer period (P = 0.0001) and were also hospitalized for longer (P = 0.0001) than the control group. The long-term survival of patients who suffered PMI after aortic surgery was significantly worse than the control group (P < 0.0001, median 53 vs. 84 months), independent of clinical ischemia-associated symptoms. - Conclusions - PMI after aortic surgery not only affects long-term survival, but also correlates with worsening of surgical outcome. Thus, meticulous preoperative risk stratification is required for high-risk patients, together with routine postoperative monitoring of troponin levels after aortic surgery.
Gesehen am 06.12.2022